Antibacterial Peptide from Chymotrypsin Hydrolysate of Jatropha Seeds with RP-HPLC Fractionation - Andriana, Zehan; Wahyuningsih, Tutik Dwi; Raharjo, Tri Joko (Universitas Jenderal Soedirman, 2023)
Antimicrobial peptide (AMP), as a new antibiotic agent, has promising prospects in overcoming the problem of resistance. AMP production can be carried out by proteolytic enzymes. Protein from castor bean (R. communis) is toxic, so it can potentially be a source of AMP. This study aims to obtain protein hydrolysate from the castor bean (R. communis) using several extraction methods, including SDS dialysis, SDS-gel filtration, trifluoroacetic acid (TFA), and acetone precipitation. Chymotrypsin enzyme was used to hydrolyze the protein, and the peptide hydrolysate was fractionated using RP-HPLC. The peptide fraction was tested for its antibacterial activity by agar diffusion and microdilution methods, and the most active fraction was identified for its amino acid sequence by LC-HRMS. The results showed that the acetone precipitation extraction method was the best method, with a degree of hydrolysis of 83.9%. The active fractions 6 and 10 of RP-HPLC had IC50 values of 14.1 and 14.5 µg/mL for E. coli and 13.3 and 14.4 µg/mL for S. aureus, respectively. NVLRGKGMASL peptides were found in fraction 10, and GIILLSSK, NMIAKR, and LLDILTKK peptides were found in fraction 6 with an alpha helix secondary structure that can cause membrane damage. The peptides NVLRGKGMASL, GIILLSSK, NMIAKR, and LLDILTKK are thought to have potential as antibacterial compounds.